Decreased Tissue Kallikrein Levels and the Risk of Ischemic Stroke: A Community-Based Cross-Sectional Study in China - Ran X; Wang DW; Yu Z; Wu R; Zhang Q (Dove Medical Press, 2022)
Xiao Ran,1 Dao Wen Wang,2 Zhen Yu,1 Rongxue Wu,3 Qin Zhang4 1Department of Emergency, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, Hubei, People's Republic of China; 2The Institute of Hypertension and Department of Internal Medicine, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, Hubei, People's Republic of China; 3Department of Biological Sciences Division/ Cardiology, University of Chicago, Chicago, IL, 60637, USA; 4Department of Anesthesiology, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, Hubei, People's Republic of ChinaCorrespondence: Qin Zhang Email qzhang8@tjh.tjmu.cnAim: Tissue kallikrein (TK) exerts protective effects on cardiac cerebrovascular diseases (CCVDs). Changes in TK level in plasma are associated with ischemic stroke and coronary artery disease (CAD); however, a causal correlation could not be established. Therefore, we investigated the association between TK levels and CCVDs in a community-based cross-sectional study in China.Methods: A total of 6043 subjects (4242 men and 1801 women) were enrolled in this community-based cross-sectional study. Then, TK levels were measured using an enzyme-linked immunosorbent assay kit. Multivariate linear regression model and logistic regression were used to assess the correlations between TK levels and CCVDs. Subsequently, the receiver operating characteristic (ROC) curve was drawn to assess the value of TK level in evaluating the risk of ischemic stroke. Finally, the influence of various medications was evaluated on TK levels.Results: The TK level was significantly lower in subjects with ischemic stroke (P < 0.001) and hypertension (P < 0.001) and negatively associated with ischemic stroke (P < 0.001) but not associated with hypertension, coronary heart disease, and diabetes compared to the traditional risk factors. The diagnostic accuracy for ischemic stroke, as quantified by the area under the curve, was 0.892 (95% CI, 0.884- 0.900) for TK level, deeming it as a promising assessment tool. Moreover, no appreciable influence of various drugs therapy was found in TK levels (P = 0.222) except for those taking antilipemic agents.Conclusion: TK is a strong and independent endogenous protective factor against ischemic stroke in the Chinese population and could be a promising biomarker for the risk of ischemic stroke.Keywords: tissue kallikrein, ischemic stroke, cardiac cerebral vascular disease, risk factor